Methanol Aromatization over Zn and Ce Modified Hierarchical ZSM-5 Catalysts: Effect of Ce as a Promoter - Zhenhao Wei; Yufan Ji; Yiping Huang; Jingjing Huang; Yunguo Huang; Changhai Yue; Junzhou Li; Mingwei Tang; Yunfang Liu; Hanfei Liu; Hao Zhu; Kai Zhu; et al. (Advances in Materials Science and Engineering)
Zinc (Zn) and cerium (Ce) modified hierarchical ZSM-5 (HZ) catalysts were prepared by incipient wetness impregnation, and their catalytic performances in methanol to aromatics reaction were evaluated in a fixed-bed reactor operating at 400°C under 0.1 MPa and WHSV of 1.0 h−1. The structure, acidity, and state of Zn species of the Zn/Ce modified HZ catalysts were investigated via several characterization techniques, including XRD, NH3-TPD, H2-TPR, nitrogen adsorption, and XPS. The results showed that the aromatization activity of 2 wt% Zn-modified HZ (2% Zn/HZ) could be significantly enhanced by loading 0.6 wt% Ce, which was mainly attributed to the increase in surface ZnOH+ species. Moreover, it was found that Ce inhibited pore blockage caused by Zn. Consequently, compared to 2% Zn/HZ, 2% Zn-0.6% Ce/HZ exhibited higher aromatic selectivity and longer catalyst lifetime.